Ring‐Like Defect Formation in N‐Type Czochralski‐Grown Silicon Wafers during Thermal Donor Formation. Issue 4 (18th December 2020) - Basnet, Rabin; Sio, Hang; Siriwardhana, Manjula; Rougieux, Fiacre E.; Macdonald, Daniel
Abstract : This article presents experimental and simulation studies on the formation of recombination‐active ring‐like defects during thermal donor (TD) formation at 450 °C in n‐type Czochralski‐grown silicon wafers. With increasing anneal duration from 1 to 24 h, the resistivity and interstitial oxygen concentration of samples decrease, consistent with the formation of TDs. However, after a subsequent TD annihilation treatment, the resistivity recovers completely, while the interstitial oxygen concentration recovers only partially. Furthermore, the wafers exhibit ring‐like defects in photoluminescence images after the TD generation and remain persistent even after annihilation treatment. By applying a tabula rasa (TR) treatment prior to TD generation anneals, the net loss of interstitial oxygen is reduced, and the incubation time of the ring‐like defects is extended in comparison to as‐grown wafers. Finally, to investigate the possibility of low‐temperature precipitation, simulation of oxygen precipitation (OP) kinetics during the 450 °C annealing steps is performed using an enhanced effective diffusivity of oxygen. These simulations demonstrate that OP can occur simultaneously during TD formation, resulting in recombination‐active ring‐like defects. Abstract : The simultaneous formation of ring‐like defects and thermal donors at a 450 °C anneal is experimentally elucidated. The results are then corroborated by adopting an enhanced effective diffusivity of oxygen at 450 °C together with an oxygen precipitation (OP) model to simulate OP kinetics during the 450 °C annealing steps.